Comparison between the effects of syzygium jambolanum leaf and fruit xxtracts on estrogen positive and estrogen negative breast cancer cell lines - Thliamplam, U.M.; Kuppusamy, U.R.; Kanthimathi, M.S.; Wiart, C. (2006)
Medicinal plants have widely been used to treat different kinds of ailments including cancer. Syzygium jambolanum, Linn (Myrtaceae) is a tropical plant used traditionally in the treatment of diabetes. However the effect of this plant on cancer has not been reported. Breast cancer is the most prevalent type of cancer among women and the incidence of this cancer has increased significantly around the world. In the present study, aqueous extract of S. jambolanum leaves and methanolic extract of its fruits were tested on breast cancer (MCF-7 and MDA-MB-231) cell lines for anti-proliferative effect. The MTT (3-4,5-Dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide) assay was used to quantitate the viable cells. The aqueous extract of S. jambolanum leaves and the methanolic extract of the fruits exerted dose-dependent inhibition (dose range of 100-500 Î¼g/ml) on both cell lines. The leaf extract exerted more potent inhibitory effect on the MDA-MB-231 (estrogen negative) cell line as well as the MCF-7 (estrogen positive) compared with the methanolic extract of the fruit. The concentration of leaf extract that caused 50% inhibition (IC50) of MDA-MB-231 was 270 Î¼g/ml. The IC50 for the rest of the incubations could not be determined.